0831 Sleep, Circadian, and Cognitive Dysfunction in Cirrhotic Patients Waitlisted for Liver Transplant. (12th April 2019) - Kim, Minjee; Maas, Matthew B; Reid, Kathryn J; Peipert, John D; Liotta, Eric M; Ladner, Daniela P; Zee, Phyllis C
Abstract: Introduction: Sleep and circadian disruption is commonly reported in patients with liver cirrhosis, but it has not yet been systematically characterized before and after liver transplant (LT). Up to 80% of cirrhotic patients suffer from cognitive impairment, and post-LT improvement is inconsistent. Associations between the timing and magnitude of sleep, circadian, and cognitive dysfunction before and after LT are unknown. As the first step of a longitudinal observational study, we aimed to characterize pre-LT sleep, circadian rhythm, and cognition. Methods: 44 stable cirrhotic patients (23 males, age 55±12) waitlisted for LT wore a wrist actigraphy for 14 consecutive days at home and completed validated sleep questionnaires (PROMIS) and cognitive assessment (NIH Toolbox). 72 age/gender-matched healthy controls wore a wrist actigraphy. Sleep was scored using actigraphy and sleep diaries. Rest-activity patterns (interdaily stability (IS), intradaily variability (IV), relative amplitude (RA), L5/M10 midpoint) were derived using non-parametric analyses. Cognitive performance was scored against demographic-matched population norms as T-scores. Results: : Rest-activity patterns in cirrhotic patients were more fragmented (IV 0.99±0.23 vs. 0.84±0.22, p =0.001), less stable (IS 0.35±0.16 vs. 0.47±0.18, p =0.002), lower in amplitude (RA 0.69±0.19 vs. 0.84±0.20, p <0.001), and delayed (M10 midpoint 13:27:28±2:40:50 vs. 15:02:41±3:22:13, p =0.007) compared to controls. Impaired sleep quality in cirrhotics was evidenced by both PROMIS questionnaires (Sleep Disturbance T-score 54.7±10.4, Sleep-Related Impairment T-score 54.2±9.9) and actigraphy (sleep efficiency 83.6±7.8% vs. 89.8 ±3.5%, p <0.001; wake after sleep onset 80.2±41.6min vs. 40.0±14.4min, p <0.001; sleep period time 500.3±75.2min vs. 455.4±49.9min, p =0.001; sleep offset 08:00:04±01:35:42 vs. 07:23:31±01:00:01, p =0.026) compared to controls. Cognition was impaired by one SD below demographic-matched population norm (T-score 39.5±8.6 vs. 50±10, p <0.001). No significant association was found between cognitive function and sleep/circadian variables. Conclusion: Sleep, circadian rhythms, and cognition were impaired in cirrhotic patients compared to controls. In cross-sectional analysis, a clear association between sleep/circadian disturbance and cognition is not evident, although both are known to fluctuate in severity. Longitudinal data will examine pre-to-post-LT changes in sleep, circadian rhythm, and cognition and their impacts on health outcomes. Support (If Any): none